The Influence of Digital Talent Development and Green Innovation and The Use of Green Innovation As Mediation To Measure Data Centre Performance - Rifa Herdian; Mohammad Syamsul Maarif; Anggraini Sukmawati; Irman Hermandi (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: Data Centre industry activity in Asia Pacific is experiencing significant growth, driven by the increasing adoption of cloud technology and data-driven solutions. Telkom Group faces the biggest challenges in data centre development in the form of compliance with increasingly stringent sustainability regulations, increasing demand for skilled and experienced talent, as well as the challenge of adopting green innovation as a solution to sustainability issues. Data Centre Managers need to encourage talent who are capable of developing innovations to reduce carbon emissions, as well as the need for very high electrical power.Purpose: The purpose of this study is to examine how data center performance is impacted by green innovation and digital talent development. It also looks at how green innovation may help data center companies become more competitive, increase operational sustainability, and improve energy efficiency in the face of regulatory obstacles and a lack of skilled digital workers.Design/methodology/approach: The research uses Partial Least Square (PLS) analysis using SmartPLS software to test various related variables. Data collection used a survey method which included in-depth interviews and questionnaires. Respondents are Data Center Managers, Digital Talent Development Experts, Data Center Operational and Technical Teams, and Experts and Consultants in the Field of Green Technology and Data Centers.Findings/Result: By increasing energy efficiency and reducing negative impacts on the environment, green innovation greatly impacts data centre performance. Data centres can significantly reduce their energy consumption and carbon emissions by implementing renewable energy and efficient cooling systems. This research emphasizes the importance of green innovation and digital transformation to improve data centre performance, and emphasizes the positive benefits of green innovation on data centre performance. The research also shows that incorporating environmentally friendly practices and advanced technologies into data centre operational strategies can provide major benefits in terms of energy efficiency, resource efficiency and cost efficiencyConculusions: Through modern technology, carbon reduction, and energy efficiency, digital transformation and green innovation greatly improve data center performance. Reliability, cost effectiveness, and sustainability are increased by integrating automation, efficient cooling, and renewable energy. According to this survey, green innovation is essential for streamlining operations and encouraging eco-friendly data center practices.Originality/value (State of the art): This study highlights the unique role of green practices in boosting energy efficiency, operational sustainability, and competitiveness in the data center business despite regulatory and talent shortages by using renewable energy and modern technologies. Keywords: data centre performance, digital transformation, digital talent, green innovation, green energy